PENGARUH KINERJA GURU FIKIH TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI MTS MUHAMMADIYAH LEMPANGANG GOWA - Nur Faisal; Muhammad Yahdi; Muhammad Rusmin B; Andi Achruh; Abudzar Al Qifari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the phenomenon of suboptimal student learning motivation at MTs Muhammadiyah Lempangang Gowa. The focus of this research is to examine the influence of fiqh teacher performance on student learning motivation. This study aims to describe the performance of fiqh teachers, student learning motivation, and analyze the influence between the two variables. The method used is quantitative ex post facto with a simple paradigm design. The study population involved 73 eighth grade students, with data collection techniques using questionnaires (Likert scale) and documentation. Data were analyzed using descriptive statistics and simple linear regression through the assistance of SPSS. The results showed that the performance of fiqh teachers was in the moderate category (71%), and student learning motivation was also in the moderate category (57%). The results of the hypothesis test showed a significance value of 0.001 < 0.05, which means that teacher performance has a positive and significant effect on learning motivation by 48%, while the remaining 52% is influenced by other factors. In conclusion, the performance of fiqh teachers has an important role in encouraging student learning activity and enthusiasm. Teachers are expected to continue to improve the quality of their learning so that student motivation is maintained and increases effectively.